Distributed Computing and Internet Technology: 11th International Conference, ICDCIT 2015, Bhubaneswar, India, February 5-8, 2015. Proceedings - Natarajan, Raja (Springer, 2015)
This book constitutes the refereed proceedings of the 11th International Conference on Distributed Computing and Internet Technology, ICDCIT 2015, held in Bhubaneswar, India, in February 2015. The 12 revised full papers presented together with 30 short papers and 9 invited talks in this volume were carefully reviewed and selected from 221 submissions. The papers cover topics such as distributed computing and algorithms; internet technologies and Web services; secure computing and communication; cloud computing; information retrieval and recommender systems and societal applications.